Investigating causality between liability to ADHD and substance use, and liability to substance use and ADHD risk, using Mendelian randomization. (16th November 2019) - Treur, Jorien L.; Demontis, Ditte; Smith, George Davey; Sallis, Hannah; Richardson, Tom G.; Wiers, Reinout W.; Børglum, Anders D.; Verweij, Karin J.H.; Munafò, Marcus R.
Abstract: Attention‐deficit hyperactivity disorder (ADHD) has consistently been associated with substance use, but the nature of this association is not fully understood. To inform intervention development and public health messages, a vital question is whether there are causal pathways from ADHD to substance use and/or vice versa. We applied bidirectional Mendelian randomization, using summary‐level data from the largest available genome‐wide association studies (GWAS) on ADHD, smoking (initiation, cigarettes per day, cessation, and a compound measure of lifetime smoking), alcohol use (drinks per week, alcohol problems, and alcohol dependence), cannabis use (initiation), and coffee consumption (cups per day). Genetic variants robustly associated with the "exposure" were selected as instruments and identified in the "outcome" GWAS. Effect estimates from individual genetic variants were combined with inverse‐variance weighted regression and five sensitivity analyses (weighted median, weighted mode, MR‐Egger, generalized summary data–based MR, and Steiger filtering). We found evidence that liability to ADHD increases likelihood of smoking initiation and heaviness of smoking among smokers, decreases likelihood of smoking cessation, and increases likelihood of cannabis initiation. There was weak evidence that liability to ADHD increases alcohol dependence risk but not drinks per week or alcohol problems. In the other direction, there was weak evidence that smoking initiation increases ADHD risk, but follow‐up analyses suggested a high probability of horizontal pleiotropy. There was no clear evidence of causal pathways between ADHD and coffee consumption. Our findings corroborate epidemiological evidence, suggesting causal pathways from liability to ADHD to smoking, cannabis use, and, tentatively, alcohol dependence. Further work is needed to explore the exact mechanisms mediating these causal effects. Abstract : We applied bidirectional Mendelian randomization (see Figure) to summary‐level data from the largest available genome‐wide association studies on ADHD, smoking, alcohol use, cannabis use and coffee consumption, to investigate whether there are causal pathways from ADHD to substance use and/or vice versa. We found evidence that liability to ADHD increases likelihood of smoking and cannabis initiation and heaviness of smoking, and decreases likelihood of smoking cessation, as well as weak evidence that liability to ADHD increases alcohol dependence risk